Improved Structure and Three-dimensional Numerical Analysis of Diesel Nozzle - LI Ming-hai; YIN Hai-tin (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
First the study shows flow area can enlarge and turbulence generated by energy loss can reduce as the fuel injection hole chamfering，when spray nozzles are designed in the cone by analyzing and calculating the parameters of a high-power diesel. Then the investigation is created that it is about the pressure maps, velocity maps and discharge maps after the models are imported into the fluid software. The results about the numerical simulation test and verify the validity of the improved structure providing a reference for domestic peers. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1401